Food allergy consumption according to halalan tayyiban perspective: a review - Ramli, Mohd Hasli; Rosman, Arieff Salleh; Khan, Aqeel; Jamaludin, Mohd Aizat; Ahmad Fadzlillaah, Nurrulhidayah; Hassan, Ahmad Muhyuddin; Samat@Darawi, Abdul Basit; Mohammedahmed Bayoumi, Kawthar Abdalla (Centivens Institute of Innovative Research, 2021)
Food allergies are the effects of a detrimental reaction from the body's immuntive system on certain types of food that are considered harmful to the body. Food allergies are also considered a critical issue in food safety and food quality management systems. In fact, the issue of food allergy consumption is also discussed from the aspects of medical and food industry to prevent any risk of consuming food that is harmful to consumers. Generally, the implementation of the concept of ‘halalan tayyibban’ only focuses on the study of raw materials, food processing activities and storage of final ingredients from illegal, clean and safe to be eaten elements. However, this aspect of food allergy intake is not discussed comprehensively based on the perspective of ‘Halalan Tayyiban’. Therefore, this article uses a qualitative approach through document analysis to describe the importance of consuming allergic foods according to the perspective of ‘halalan tayyiban’ in-depth. In addition, the aspects of food allergy control and management through food quality management system are also discussed. This study also suggests that the assessment of risk analysis and food allergy management be discussed in more depth according to the Islamic perspective based on the sources of the Quran and hadith. Hence, this study will have a positive impact on improving the halal auditing process and strengthening the integrity of food product status in line with the concept of ‘halalan tayyiban.’